Imunolocalização de Wnt-1, β-Catenina e c-Myc em adenomas e adenocarcinomas de células basais de glândula salivar - Servato, João Paulo Silva (2011)
Introduction: The immunohistochemical detection of nuclear β-Catenin has been widely used to demonstrate activation of the canonical Wnt/β- Catenin pathway in a wide variety of human cancers, including basal cell adenoma and basal cell adenocarcinoma salivary gland, although the immunolocalization of other proteins of this pathway is still unknown. The objective of this study was to access the immunolocalization of Wnt1, β-catenin and c-Myc in the basal cell adenoma and basal cell adenocarcinoma. Materials and Methods: We studied the immunolocalization of Wnt1, β-catenin and c-Myc in a series of four 28 basal cell adenoma and four basal cell adenocarcinoma, by immunohistochemistry using the streptavidin-biotin peroxidase method. Results: Wnt1 was positive in 14 cases (50.0%) always in a small proportion of cells, low intensity and restricted to the cytoplasm. β-Catenin was detected in the nucleus of tumor cells in all cases, being the prevalent pattern in 67.9% of them. In tumors with tubular differentiation, this finding was generally restricted to abluminal cells. C-myc was detected in 20 cases (71.4%) and it varied in proportion and intensity of tumor cells, always in cytoplasmic pattern. We could not identify any association between the expressions of these molecules in basal cell adenomas. Two recurrent cases showed high levels of Quickscore. For basal cell adenocarcinomas, the findings were similar, except that it was not common nuclear staining of β-Catenin. Conclusions: Our results confirm that the nuclear compartmentalization of β- Catenin is a feature of basal cell adenomas, which may be useful in their distinction to the basal cell adenocarcinoma. On the other hand, this feature cannot be due to activation of the canonical Wnt / β-Catenin, or at least the expression of its main agonist (Wnt1). Other agonists of this pathway remain to be investigated, such as Wnt3 and Wnt8. Similarly, the possible effect of the nuclear localization of β-catenin does not appear to be mediated by the expression of c-Myc.